Experimental Analysis on the Influence of Nozzle Geometry Over the Dispersion of Liquid N-Dodecane Sprays - Payri, Raul; Salvador, Francisco Javier; Gimeno, Jaime; Viera, Juan P. (Frontiers in Mechanical Engineering, 2015)
Understanding and controlling mixing and combustion processes is fundamental in order to face the challenges set by the ever more demanding pollutant regulations and fuel consumption standards of direct injection diesel engines. The fundamentals of these processes haven been long studied by the diesel spray community from both experimental and numerical perspectives. However, certain topics such as the influence of nozzle geometry over the spray atomization, mixing and combustion process are still not completely well understood and predicted by numerical models. The present study seeks to contribute to the current understanding of this subject, by performing state-of-the-art optical diagnostics to liquid sprays injected through two singe-hole nozzles of different conicity. The experiments were carried out in a nitrogen-filled constant-pressure-flow facility. Back pressures were set to produce the desired engine-like density conditions in the chamber, at room temperature. The experimental setup consists in a diffused back illumination setup with a fast pulsed LED light source and a high-speed camera. The diagnostics focused on detecting the liquid spray contour and evaluating the influence of nozzle geometry over the time-resolved and quasi-steady response of the spray dispersion, at similar injection conditions. Results show a clear influence of nozzle geometry on spray contour fluctuations, where the cylindrical nozzle seems to produce larger dispersion in both time-resolved fluctuations and quasi-steady values, when compared to the conical nozzle. This evidences that the turbulence and radial velocity profiles originated at the cylindrical nozzle geometry are able to affect not only the microscopic scales inside the nozzle, but also macroscopic scales such as the steady spray. Observations from this study indicate that the effects of the flow characteristics within the nozzle are carried on to the first millimeters of the spray, in which the rest of the spray formation downstream is pre-defined.